High-stability foam glass and preparation method thereof

By processing waste materials like waste cullet, graphite electrodes, and aluminum ash slag through coating and magnetization, the method produces high-stability foam glass with improved mechanical properties and reduced pollution.

CN119118522AInactive Publication Date: 2024-12-13SHENZHEN XIAOSHENG YICHUANG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411249562.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for preparing foam glass from waste materials suffer from low utilization rates, poor stability, and high pollution risks due to unprocessed waste components, particularly heavy metals and dioxins.

Method used

A method involving the use of waste cullet, waste graphite electrodes, and waste aluminum ash slag, where the graphite electrodes are coated with ferroferric oxide and magnetized, and the aluminum ash slag is calcined in stages, followed by a series of processing steps to produce high-stability foam glass.

Benefits of technology

The method enhances the stability and reduces pollution by minimizing agglomeration and effectively solidifying heavy metals, resulting in improved mechanical properties and reduced environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031871090000071
    Figure BDA0005031871090000071
  • Figure BDA0005031871090000081
    Figure BDA0005031871090000081
Patent Text Reader

Abstract

The invention discloses high-stability foam glass and a preparation method thereof, and relates to the technical field of glass foam. According to the method, the waste graphite electrode is firstly subjected to ball milling into micron-sized fine powder, then a layer of ferroferric oxide is chemically deposited on the surface of the micron-sized fine powder, mutual adsorption of the graphite electrode powder is weakened, then the coated graphite electrode is magnetized, the graphite electrode has the same magnetism, the agglomeration effect is greatly reduced due to repulsive force, and the structure is more stable. Secondly, the waste aluminum ash is subjected to segmented high-temperature calcination, and harmful components are volatilized at high temperature through primary calcination; and the second-stage calcination is combined with microwaves, so that silicon-containing salt in the aluminum ash forms silicon oxide, and the transition of the foam glass melt from a glassy state to a crystalline state is reduced. Meanwhile, ferroferric oxide in a graphite electrode coating film can be combined with heavy metal in the waste aluminum ash residues, so that heavy metal ions are effectively solidified, and pollution is reduced. The prepared glass foam has the effects of high stability and less pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foam glass, in particular to high-stability foam glass and a preparation method thereof. Background Art

[0002] At present, the waste generated by the incineration of hazardous waste with high calorific value can be divided into two categories: bottom ash and fly ash. The ash from the incineration of hazardous waste contains pollutants such as heavy metals and dioxins. If it is not properly handled, it will cause serious secondary pollution to the human living environment. Foam microcrystalline glass has excellent properties such as low density, high strength, low thermal conductivity, waterproofness, and heat preservation. It can be used as building wall insulation materials and self-supporting materials. At present, there are many reports on the preparation of foam microcrystalline glass using solid wastes such as waste glass, fly ash, bottom ash, metal tailings, red mud, and granite tailings.

[0003] However, the existing technology usually melts solid waste into glass at high temperature, obtains basic glass powder through quenching and grinding, then mixes the basic glass powder with additives such as foaming agent and foam stabilizer to prepare a body, and finally obtains foamed microcrystalline glass through sintering or nucleation-crystallization-annealing heat treatment. How to improve the utilization rate of waste products, reduce the harmful substances in waste products that affect product quality, and improve the stability of the product foam glass is the focus of the present invention. Summary of the invention

[0004] The purpose of the present invention is to provide a high-stability foam glass and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-stability foam glass, which is made from waste cullet, waste graphite electrodes, and waste aluminum ash slag as raw materials, and the waste materials are subjected to simple secondary processing; the cullet is ball-milled, the waste aluminum ash slag is calcined at high temperature in stages, the waste graphite electrodes are coated and magnetized, and then foaming and other steps are performed to obtain the foam glass.

[0006] Furthermore, the waste graphite electrode coating magnetization is performed by grinding the waste graphite electrode into fine powder, coating the surface with a ferroferric oxide film, and then magnetizing it through electric field treatment.

[0007] Furthermore, a method for preparing high-stability foam glass comprises the following preparation steps:

[0008] (1) crushing the discarded graphite electrode, throwing it into a ball mill, ball milling for 1-2 hours, and grinding it into a graphite electrode powder with a particle size of 80-120 μm; dispersing 100 parts of the graphite electrode powder in 500 parts of deionized water, and ultrasonicating at 40kHz for 30 minutes; then, under the protection of inert gas, adding 5-30 parts of ferric chloride and ferrous chloride, wherein the molar ratio of ferric chloride to ferrous chloride is 2:1, adjusting the pH value of the solution to 10, heating to 80-100°C, stirring and reacting for 6-8 hours, centrifuging at 10000 rpm for 20 minutes after the reaction, washing the solid with deionized water three times, drying at 50°C for 5 hours, and then calcining at 500-600°C for 2-3 hours to obtain coated graphite electrode powder; placing the coated graphite electrode powder in batches in an electromagnetic coil composed of an insulated wire passing direct current, so that the irregular magnetic domains in the coating are aligned, and the current is set to 500 mA to obtain magnetized graphite electrode powder;

[0009] (2) calcining the waste aluminum slag at 1000-1400° C. for 60-180 min, cooling it to 25° C. at room temperature after calcination to obtain the first-stage calcined aluminum slag; then calcining the first-stage calcined aluminum slag in a second stage by microwave sintering at 900-1100° C. for 10-30 min; cooling it to 25° C. at room temperature after the second-stage calcination to obtain the second-stage calcined aluminum slag;

[0010] (3) The waste broken glass is washed twice with deionized water, and then dried at 50°C for 2h; the dried broken glass is simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax, and sodium dodecyl sulfate are mixed in a mass ratio of 50-70:30-40:4-6:0.2-0.6, and then ball-milled until the mixed powder particle size is 80μm, and then 3-6 parts of magnetized graphite electrode powder are added, mixed evenly, added to a heat-resistant steel mold and pressed flat at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold is placed in a heating furnace, and a foam melt is obtained by high-temperature melting and foaming; the melting and foaming temperature is 860-960°C, and the insulation time is 40min; then the foam melt is cooled to 550°C, annealed for 3-6h, and then cooled to room temperature with the furnace to obtain foam glass.

[0011] Furthermore, the ball milling conditions in step (1) are: using 5 mm ceramic balls as ball milling media and the ball milling speed is 300-500 rpm.

[0012] Furthermore, the inert gas in step (1) is preferably nitrogen.

[0013] Furthermore, the magnetization time in step (1) is 3-5 min.

[0014] Furthermore, the heating rate in step (2) is 30-50°C / min.

[0015] Furthermore, the microwave power during microwave calcination in step (2) is 60 GHz.

[0016] Furthermore, the ball milling conditions in step (3) are: using 3 mm ceramic balls as ball milling media and the ball milling speed is 800 rpm.

[0017] Furthermore, the annealing cooling rate in step (3) is 5°C / s.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention utilizes waste broken glass, waste graphite electrodes and waste aluminum ash slag as raw materials, and performs simple secondary processing on the waste materials; broken glass is ball-milled, waste aluminum ash slag is calcined at high temperature in stages, waste graphite electrodes are coated and magnetized, and then foaming and other steps are performed to obtain foamed glass, so as to achieve the effects of high stability and less pollution.

[0020] First, the waste graphite electrode is ball-milled into micron-sized fine powder, and then a layer of ferroferric oxide is chemically deposited on its surface. The ferroferric oxide coating reduces the energy of the occupied state of d-electrons and increases the energy of the unoccupied state, weakening the mutual adsorption of graphite electrode powders, thereby reducing their agglomeration phenomenon; on this basis, the coated graphite electrode is magnetized, and the magnetism of ferroferric oxide is used to make the graphite electrode subsequently added to the glass powder have the same magnetism. Due to a certain repulsive force between them, the agglomeration effect is greatly reduced, so that the prepared foam glass has good pore uniformity, a more stable structure, and improved mechanical properties;

[0021] Secondly, the waste aluminum ash slag is calcined in stages at high temperature. The primary calcination is mainly to volatilize the harmful components in the waste aluminum ash slag at high temperature; the secondary calcination is combined with microwaves to convert the silicon salts in the aluminum ash slag into silicon oxides. In this way, when the glass is sintered using the aluminum ash slag that has been calcined in stages, the temperature is lower, reducing the transformation of the foam glass melt from the glassy state to the crystalline state; at the same time, the ferroferric oxide in the graphite electrode coating can combine with the heavy metals in the waste aluminum ash slag, and the ion stacking on its octahedron can be replaced by the heavy metal ions, so that the heavy metal ions are effectively solidified, effectively reducing the leaching of heavy metals during the use of the glass, thereby reducing pollution. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a high-stability foam glass prepared in the following examples as follows:

[0024] Stability: The foam glass in the embodiments and comparative examples was cut into products according to JC_T647-2014 Foam Glass Insulation Products and subjected to compressive strength test.

[0025] Heavy metal leaching: The foam glass in the examples and comparative examples was tested for heavy metal leaching with reference to GB5085.3-2007.

[0026] Example 1

[0027] (1) crushing the waste graphite electrode, throwing it into a ball mill, ball milling for 1 hour, using 5 mm ceramic balls as ball milling media, ball milling speed of 300 rpm, grinding into graphite electrode powder with a particle size of 80 μm; dispersing 100 parts of graphite electrode powder in 500 parts of deionized water, and ultrasonicating at 40 kHz for 30 minutes; then, under the protection of nitrogen gas, adding 5 parts of ferric chloride and ferrous chloride, the molar ratio of ferric chloride to ferrous chloride is 2:1, adjusting the pH value of the solution to 10, heating to 80°C, stirring for 6 hours, centrifuging at 10000 rpm for 20 minutes after the reaction, washing the solid with deionized water 3 times, drying at 50°C for 5 hours, and then calcining at 500°C for 2 hours to obtain coated graphite electrode powder; placing the coated graphite electrode powder in batches in an electromagnetic coil composed of an insulated wire passing direct current, so that the direction of the irregular magnetic domains in the coating is consistent, the current is set to 500 mA, the magnetization time is 3 minutes, and magnetized graphite electrode powder is obtained;

[0028] (2) calcining the waste aluminum slag at 1000° C. for 60 min at a heating rate of 30° C. / min, and cooling to 25° C. at room temperature after calcination to obtain the first-stage calcined aluminum slag; then calcining the first-stage calcined aluminum slag in a second stage by microwave sintering at a microwave power of 60 GHz and a heating rate of 30° C. / min at 900° C. for 10 min; and cooling to 25° C. at room temperature after the second-stage calcination to obtain the second-stage calcined aluminum slag;

[0029] (3) The waste broken glass was washed twice with deionized water and then dried at 50°C for 2h; the dried broken glass was simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax and sodium dodecyl sulfate were mixed in a mass ratio of 50:30:4:0.2, and then ball milled with 3mm ceramic balls as ball milling media at a ball milling speed of 800rpm until the mixed powder particle size was 80μm, and then 3 parts of magnetized graphite electrode powder were added and mixed evenly, and pressed flat with a heat-resistant steel mold at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold was placed in a heating furnace, and a foam melt was obtained through high-temperature melting and foaming; the melting and foaming temperature was 860°C, and the heat preservation time was 40min; then the foam melt was cooled to 550°C at a cooling rate of 5°C / s, annealed for 3h, and then cooled to room temperature with the furnace to obtain foam glass.

[0030] Example 2

[0031] (1) The discarded graphite electrode was crushed and then thrown into a ball mill for 1.5 hours, with a 5 mm ceramic ball as the ball milling medium and a ball milling speed of 400 rpm, to grind into a graphite electrode powder with a particle size of 100 μm; 100 parts of the graphite electrode powder were dispersed in 500 parts of deionized water and subjected to 40 kHz ultrasonic treatment for 30 minutes; then, under the protection of nitrogen gas, 15 parts of ferric chloride and ferrous chloride were added, the molar ratio of ferric chloride to ferrous chloride was 2:1, the pH value of the solution was adjusted to 10, and the solution was heated. to 90°C, stirred for reaction for 7h, centrifuged at 10000rpm for 20min after the reaction, washed the solid with deionized water 3 times, dried at 50°C for 5h, and then calcined at 550°C for 2.5h to obtain coated graphite electrode powder; the coated graphite electrode powder was placed in batches in an electromagnetic coil composed of an insulated wire passing direct current, so that the direction of the irregular magnetic domains in the coating was consistent, the current was set to 500mA, and the magnetization time was 4min to obtain magnetized graphite electrode powder;

[0032] (2) calcining the waste aluminum slag at 1200° C. for 120 min at a heating rate of 40° C. / min, and cooling to 25° C. at room temperature after calcination to obtain the first-stage calcined aluminum slag; then calcining the first-stage calcined aluminum slag in a second stage by microwave sintering at a microwave power of 60 GHz and a heating rate of 40° C. / min at 1000° C. for 20 min; and cooling to 25° C. at room temperature after the second-stage calcination to obtain the second-stage calcined aluminum slag;

[0033] (3) The waste broken glass was washed twice with deionized water and then dried at 50°C for 2h; the dried broken glass was simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax and sodium dodecyl sulfate were mixed in a mass ratio of 60:35:5:0.4, and then ball milled with 3mm ceramic balls as ball milling media at a ball milling speed of 800rpm until the mixed powder particle size was 80μm, and then 4.5 parts of magnetized graphite electrode powder were added and mixed evenly, and pressed flat with a heat-resistant steel mold at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold was placed in a heating furnace, and a foam melt was obtained through high-temperature melting and foaming; the melting and foaming temperature was 910°C, and the heat preservation time was 40min; then the foam melt was cooled to 550°C at a cooling rate of 5°C / s, annealed for 4.5h, and then cooled to room temperature with the furnace to obtain foam glass.

[0034] Example 3

[0035] (1) The discarded graphite electrode was crushed and then thrown into a ball mill for 2 h, with 5 mm ceramic balls as the ball milling medium, the ball milling speed was 500 rpm, and the graphite electrode powder with a particle size of 120 μm was ground; 100 parts of the graphite electrode powder was dispersed in 500 parts of deionized water, and ultrasonicated at 40 kHz for 30 min; then, under the protection of nitrogen gas, 30 parts of ferric chloride and ferrous chloride were added, the molar ratio of ferric chloride to ferrous chloride was 2:1, the pH value of the solution was adjusted to 10, and heated to 100°C, stirring for reaction for 8 hours, centrifuging at 10000rpm for 20 minutes after the reaction, washing the solid with deionized water for 3 times, drying at 50°C for 5 hours, and calcining at 600°C for 3 hours to obtain coated graphite electrode powder; placing the coated graphite electrode powder in batches in an electromagnetic coil composed of an insulated wire passing direct current, so that the direction of the irregular magnetic domains in the coating tends to be consistent, the current is set to 500mA, and the magnetization time is 5 minutes to obtain magnetized graphite electrode powder;

[0036] (2) calcining the waste aluminum slag at 1400° C. for 180 min at a heating rate of 50° C. / min, and cooling to 25° C. at room temperature after calcination to obtain the first-stage calcined aluminum slag; then calcining the first-stage calcined aluminum slag in a second stage by microwave sintering at a microwave power of 60 GHz and a heating rate of 50° C. / min at 1100° C. for 30 min; and cooling to 25° C. at room temperature after the second-stage calcination to obtain the second-stage calcined aluminum slag;

[0037] (3) The waste broken glass was washed twice with deionized water and then dried at 50°C for 2h; the dried broken glass was simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax and sodium dodecyl sulfate were mixed in a mass ratio of 70:40:6:0.6, and then ball milled with 3mm ceramic balls as ball milling media at a ball milling speed of 800rpm until the mixed powder particle size was 80μm, and then 6 parts of magnetized graphite electrode powder were added and mixed evenly, and pressed flat with a heat-resistant steel mold at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold was placed in a heating furnace, and a foam melt was obtained through high-temperature melting and foaming; the melting and foaming temperature was 960°C, and the heat preservation time was 40min; then the foam melt was cooled to 550°C at a cooling rate of 5°C / s, annealed for 6h, and then cooled to room temperature with the furnace to obtain foam glass.

[0038] Comparative Example 1

[0039] The difference between Comparative Example 1 and Example 2 lies in the difference in steps (1) (3), where steps (1) (3) are modified as follows: (1) the waste graphite electrode is crushed and then thrown into a ball mill, and ball milled for 1.5 h, using 5 mm ceramic balls as ball milling media, and the ball milling speed is 400 rpm to grind into a graphite electrode powder with a particle size of 100 μm; 100 parts of the graphite electrode powder are dispersed in 500 parts of deionized water, and ultrasonicated at 40 kHz for 30 min; then, under the protection of nitrogen gas, 15 parts of ferric chloride and ferrous chloride are added, the molar ratio of ferric chloride to ferrous chloride is 2:1, the pH value of the solution is adjusted to 10, heated to 90°C, stirred for reaction for 7 h, and after the reaction is completed, centrifuged at 10000 rpm for 20 min, the solid is washed 3 times with deionized water, dried at 50°C for 5 h, and then calcined at 550°C for 2.5 h to obtain a coated graphite electrode powder;

[0040] (3) The waste broken glass was washed twice with deionized water, and then dried at 50°C for 2h; the dried broken glass was simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax, and sodium dodecyl sulfate were mixed in a mass ratio of 60:35:5:0.4, and then ball milled with 3mm ceramic balls as ball milling media at a ball milling speed of 800rpm until the mixed powder particle size was 80μm, and then 4.5 parts of coated graphite electrode powder were added, mixed evenly, added to a heat-resistant steel mold and pressed flat at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold was placed in a heating furnace, and a foam melt was obtained through high-temperature melting and foaming; the melting and foaming temperature was 910°C, and the heat preservation time was 40min; then the foam melt was cooled to 550°C at a cooling rate of 5°C / s, annealed for 4.5h, and then cooled to room temperature with the furnace to obtain foam glass. The remaining steps are the same as in Example 2.

[0041] Comparative Example 2

[0042] The difference between Comparative Example 2 and Example 2 lies in the difference in steps (1) (3). Steps (1) (3) are changed to: (1) the waste graphite electrode is crushed and then thrown into a ball mill, and ball milled for 1.5 h, using 5 mm ceramic balls as the ball milling medium, and the ball milling speed is 400 rpm to grind into a graphite electrode powder with a particle size of 100 μm;

[0043] (3) The waste broken glass was washed twice with deionized water and then dried at 50°C for 2h; the dried broken glass was simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax and sodium dodecyl sulfate were mixed in a mass ratio of 60:35:5:0.4, and then ball milled with 3mm ceramic balls as ball milling media at a ball milling speed of 800rpm until the mixed powder particle size was 80μm, and then 4.5 parts of graphite electrode powder were added, mixed evenly, added to a heat-resistant steel mold and pressed flat at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold was placed in a heating furnace, and a foam melt was obtained by high-temperature melting and foaming; the melting and foaming temperature was 910°C and the heat preservation time was 40min; then the foam melt was cooled to 550°C at a cooling rate of 5°C / s, annealed for 4.5h, and then cooled to room temperature with the furnace to obtain foam glass; the remaining steps were the same as in Example 2.

[0044] Comparative Example 3

[0045] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: sintering the waste aluminum ash slag with microwave power of 60 GHz, heating rate of 40°C / min, at 1000°C for 120 min; cooling to 25°C at room temperature after the second stage calcination to prepare calcined aluminum ash slag;

[0046] (3) The waste broken glass was washed twice with deionized water and then dried at 50°C for 2h; the dried broken glass was simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, calcined aluminum ash, borax and sodium dodecyl sulfate were mixed in a mass ratio of 60:35:5:0.4, and then ball milled with 3mm ceramic balls as ball milling media at a ball milling speed of 800rpm until the mixed powder particle size was 80μm, and then 4.5 parts of magnetized graphite electrode powder were added, mixed evenly, added to a heat-resistant steel mold and pressed flat at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold was placed in a heating furnace, and a foam melt was obtained by high-temperature melting and foaming; the melting and foaming temperature was 910°C and the heat preservation time was 40min; then the foam melt was cooled to 550°C at a cooling rate of 5°C / s, annealed for 4.5h, and then cooled to room temperature with the furnace to obtain foam glass; the remaining steps were the same as in Example 2.

[0047] Comparative Example 4

[0048] The difference between Comparative Example 4 and Example 2 lies in step (2). Step (2) is modified as follows: the waste aluminum ash slag is calcined at 1200°C for 120 min at a heating rate of 40°C / min, and cooled to 25°C at room temperature after calcination, which is a first-stage calcined aluminum ash slag; the first-stage calcined aluminum ash slag is then calcined in a second stage at a heating rate of 40°C / min at 1000°C for 20 min; after the second-stage calcination, it is cooled to 25°C at room temperature to produce a second-stage calcined aluminum ash slag; the remaining steps are the same as those in Example 2.

[0049] Effect example

[0050] Table 1 below shows the performance analysis results of a high-stability foam glass using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0051] Table 1

[0052]

[0053]

[0054] From the comparison of the experimental data of the compressive strength of the embodiment and the comparative example, it can be found that the present invention ball-mills the waste graphite electrode into micron-level fine powder, and then chemically deposits a layer of ferroferric oxide on its surface. The ferroferric oxide coating reduces the energy of the occupied state of d-electrons, while increasing the energy of the unoccupied state, weakening the mutual adsorption of the graphite electrode powder, thereby reducing its agglomeration phenomenon; on this basis, the coated graphite electrode is magnetized, and the magnetism of ferroferric oxide is used to make the graphite electrode added to the glass powder later have the same magnetism, and the agglomeration effect is greatly reduced due to a certain repulsive force between each other, so that the prepared foam glass has good pore uniformity, more stable structure, and improved mechanical properties. Secondly, the present invention performs high-temperature calcination of the waste aluminum ash slag in stages, and the primary calcination is mainly to volatilize the harmful components in the waste aluminum ash slag at high temperature; the second stage calcination is combined with microwaves to form silicon oxides from the silicon-containing salts in the aluminum ash slag, so that when the aluminum ash slag that has been calcined in stages is used to sinter the glass, the temperature is lower, and the transformation of the foam glass melt from the glass state to the crystalline state is reduced. From the comparison of the experimental data of heavy metal leaching between the embodiment and the comparative example, it can be found that the ferrosoferric oxide in the graphite electrode coating of the present invention can be combined with the heavy metals in the waste aluminum ash slag, and the ion stacking on the octahedron can be replaced by the heavy metal ions, so that the heavy metal ions are effectively solidified, which effectively reduces the leaching of heavy metals in the glass during use, thereby reducing pollution.

[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high stability foam glass, characterized in that: The foam glass is made from waste broken glass, waste graphite electrodes and waste aluminum ash slag as raw materials, and the waste materials are subjected to simple secondary processing: broken glass is ball milled, waste aluminum ash slag is calcined at high temperature in stages, waste graphite electrodes are coated and magnetized, and then foaming and the like are performed to obtain the foam glass.

2. A high stability foam glass according to claim 1, characterized in that: The waste graphite electrode coating magnetization is to grind the waste graphite electrode into fine powder, coat the surface with ferroferric oxide film, and then magnetize it through electric field treatment.

3. A method for preparing high-stability foam glass, characterized in that: The method comprises the following preparation steps: (1) crushing the discarded graphite electrode, throwing it into a ball mill, ball milling for 1-2 hours, and grinding it into a graphite electrode powder with a particle size of 80-120 μm; dispersing 100 parts of the graphite electrode powder in 500 parts of deionized water, and ultrasonicating at 40kHz for 30 minutes; then, under the protection of inert gas, adding 5-30 parts of ferric chloride and ferrous chloride, wherein the molar ratio of ferric chloride to ferrous chloride is 2:1, adjusting the pH value of the solution to 10, heating to 80-100°C, stirring and reacting for 6-8 hours, centrifuging at 10000 rpm for 20 minutes after the reaction, washing the solid with deionized water three times, drying at 50°C for 5 hours, and then calcining at 500-600°C for 2-3 hours to obtain coated graphite electrode powder; placing the coated graphite electrode powder in batches in an electromagnetic coil composed of an insulated wire passing direct current, so that the irregular magnetic domains in the coating are aligned, and the current is set to 500 mA to obtain magnetized graphite electrode powder; (2) calcining the waste aluminum slag at 1000-1400° C. for 60-180 min, cooling it to 25° C. at room temperature after calcination to obtain the first-stage calcined aluminum slag; then calcining the first-stage calcined aluminum slag in a second stage by microwave sintering at 900-1100° C. for 10-30 min; cooling it to 25° C. at room temperature after the second-stage calcination to obtain the second-stage calcined aluminum slag; (3) The waste broken glass is washed twice with deionized water, and then dried at 50°C for 2h; the dried broken glass is simply crushed to obtain glass particles with a particle size of 20mm; the glass particles, secondary calcined aluminum ash, borax, and sodium dodecyl sulfate are mixed in a mass ratio of 50-70:30-40:4-6:0.2-0.6, and then ball-milled until the mixed powder particle size is 80μm, and then 3-6 parts of magnetized graphite electrode powder are added, mixed evenly, added to a heat-resistant steel mold and pressed flat at a pressure of 0.6MPa, and then covered with a heat-resistant steel isolation plate, and the mold is placed in a heating furnace, and a foam melt is obtained by high-temperature melting and foaming; the melting and foaming temperature is 860-960°C, and the insulation time is 40min; then the foam melt is cooled to 550°C, annealed for 3-6h, and then cooled to room temperature with the furnace to obtain foam glass.

4. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The ball milling conditions in step (1) are: using 5 mm ceramic balls as the ball milling medium and the ball milling speed is 300-500 rpm.

5. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The inert gas in step (1) is preferably nitrogen.

6. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The magnetization time in step (1) is 3-5 min.

7. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The heating rate in step (2) is 30-50°C / min.

8. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The microwave power during microwave calcination in step (2) is 60 GHz.

9. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The ball milling conditions in step (3) are: using 3 mm ceramic balls as ball milling media and the ball milling speed is 800 rpm.

10. The method for preparing a high-stability foam glass according to claim 3, characterized in that: The annealing cooling rate in step (3) is 5°C / s.